2020
DOI: 10.1109/access.2020.2983820
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Logit and Weibit Model in Travel Mode Choice

Abstract: To quantify travel demand, it is necessary to understand the travelers' mode choice behavior. The Logit model is widely used in travel mode choice because of its closed form. Nevertheless, the variance of the utility function is unchanged in Logit-based models, indicating that the perceived error of the traveler on the option is fixed as the utility changes, which is inconsistent with the actual situation. While in Weibit-based models, travelers' perception error of options grows with the increase of the utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This heterogeneous perception variance in the Weibit model is more reasonable than the fixed and identical variance of all routes in the Logit model, because travelers on longer routes have larger perception variances than those on shorter routes in reality (Sheffi, 1985). Some recent empirical studies have verified the above advantage of the Weibit model over the Logit model in various travel choice problems (Kurauchi and Ido, 2017;Li et al, 2020;Tinessa et al, 2020).…”
Section: Review Of Some Basics Of the Weibit Modelmentioning
confidence: 86%
“…This heterogeneous perception variance in the Weibit model is more reasonable than the fixed and identical variance of all routes in the Logit model, because travelers on longer routes have larger perception variances than those on shorter routes in reality (Sheffi, 1985). Some recent empirical studies have verified the above advantage of the Weibit model over the Logit model in various travel choice problems (Kurauchi and Ido, 2017;Li et al, 2020;Tinessa et al, 2020).…”
Section: Review Of Some Basics Of the Weibit Modelmentioning
confidence: 86%
“…Ma et al [44] proposed a nested logit joint model and found that rich people have a greater probability of commuting by taxi or driving alone. Li et al [45] comparatively analyzed travel mode choice using logit and weibit models and showed that males prefer to travel by car more than females. Al-Salih and Esztergar-Kiss [46] proposed a multinomial logit model and a nested logit model with a utility function and found that trip distance was the most significant variable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For decades, commuting behavior has been intensively studied using a variety of methodological approaches [21]. The logit model proposed by [22] is commonly used and perhaps the most prevalent when considering the choice of mode of travel [23].…”
Section: On Discrete Choice Modelingmentioning
confidence: 99%